2019
DOI: 10.1038/s41467-019-09666-0
|View full text |Cite
|
Sign up to set email alerts
|

Boosting oxygen evolution of single-atomic ruthenium through electronic coupling with cobalt-iron layered double hydroxides

Abstract: Single atom catalyst, which contains isolated metal atoms singly dispersed on supports, has great potential for achieving high activity and selectivity in hetero-catalysis and electrocatalysis. However, the activity and stability of single atoms and their interaction with support still remains a mystery. Here we show a stable single atomic ruthenium catalyst anchoring on the surface of cobalt iron layered double hydroxides, which possesses a strong electronic coupling between ruthenium and layered double hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
365
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 529 publications
(379 citation statements)
references
References 70 publications
(60 reference statements)
14
365
0
Order By: Relevance
“…The Ru XANES result revealed that the absorption edge of Ru-SA/Ti 3 C 2 T x is located between those of Ru foil and RuO 2 (Figure 2a and Figure S5, Supporting Information), indicating that the average valence for the Ru species in Ru-SA/Ti 3 C 2 T x is situated between Ru 0 and Ru 4+ . [28] In the Ru Fourier transform EXAFS (FT-EXAFS) of Ru-SA/Ti 3 C 2 T x , the main peak is observed at ≈1.50 Å (Figure 2b), which is 38% less than the RuRu bond length for the Ru foil (2.42 Å); [19] this result is in agreement with the HAADF-STEM characterization described above (Figure 1e and Figure S1, Supporting Information). Furthermore, the wavelet transform (WT)-EXAFS contour plot of Ru-SA/Ti 3 C 2 T x exhibits only one intensity maximum at 4.6 Å −1 , corresponding to RuO bonding.…”
Section: Preparation and Characterization Of The Ru-sa/ti 3 C 2 T X Csupporting
confidence: 82%
See 3 more Smart Citations
“…The Ru XANES result revealed that the absorption edge of Ru-SA/Ti 3 C 2 T x is located between those of Ru foil and RuO 2 (Figure 2a and Figure S5, Supporting Information), indicating that the average valence for the Ru species in Ru-SA/Ti 3 C 2 T x is situated between Ru 0 and Ru 4+ . [28] In the Ru Fourier transform EXAFS (FT-EXAFS) of Ru-SA/Ti 3 C 2 T x , the main peak is observed at ≈1.50 Å (Figure 2b), which is 38% less than the RuRu bond length for the Ru foil (2.42 Å); [19] this result is in agreement with the HAADF-STEM characterization described above (Figure 1e and Figure S1, Supporting Information). Furthermore, the wavelet transform (WT)-EXAFS contour plot of Ru-SA/Ti 3 C 2 T x exhibits only one intensity maximum at 4.6 Å −1 , corresponding to RuO bonding.…”
Section: Preparation and Characterization Of The Ru-sa/ti 3 C 2 T X Csupporting
confidence: 82%
“…[13] Ru-SA/Ti 3 C 2 T x exhibits a higher C dl (191.1 mF cm −2 ) than those of Ti 3 C 2 T x and Ru-NP/Ti 3 C 2 T x (43.5 and 80.7 mF cm −2 , respectively), indicating that the acidic HER activity for Ru-SA/Ti 3 C 2 T x is remarkably improved mainly related to the existence of Ru SAs. [19] To further investigate the intrinsic catalytic activity of Ru-SA/ Ti 3 C 2 T x , the turnover frequency (TOF), [25,42,43] a figure-of-merit that is independent of the surface area, is calculated according to our previous study (Figure 3d and Figures S8a and S9a, Supporting Information). Notably, the calculated TOF of Ru-SA/ Ti 3 C 2 T x is 2.67 H 2 s −1 (η = 100 mV), which is significantly greater than those of Ru-NP/Ti 3 C 2 T x and Pt/C (0.18 and 1.29 H 2 s −1 , respectively).…”
Section: Her Performance In Acidic Mediamentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, extensive efforts have been made on their miniaturization, the theoretical prediction of the activity and the mechanism. [35][36][37][38] Moreover, research regarding cluster-sized particles is progressing. Chen and Gao reported that dodecanethiolate (C12)protected Pd 6 /AC exhibits a current density 37 times higher than that of commercially available Pt/C at an applied voltage of 1.85 V ( Fig.…”
Section: O Ads / Omentioning
confidence: 99%